Life History Parameters of Fall Armyworm, Spodoptera frugiperda (J.E.Smith) on Maize in Haryana State: LIFE HISTORY PARAMETERS OF FALL ARMYWORM - Kumar, Ankit; Mehra, Swati; Jaglan, Maha singh; Yadav, Sunita; Yadav, Surender singh (Annals of Arid Zone, 2024)
The biology of fall armyworm, Spodoptera frugiperda (J.E.Smith) Lepidoptera: Noctuidae was studied at laboratory, Department of Entomology, CCS Haryana Agricultural University, Hisar during, 2020-21. Insect culture was collected from the farmers fields to get nucleus culture and for further biological parameters i.e incubation period, per cent hatchability, larval period, pupal period, sex ratio, ovipositional periods etc. The average fecundity of S. frugiperda was recorded 622.40 with 82.0 per cent hatchability. Incubation period for 2.57 days with larval period of 16.32 days. Pupal period was observed as 7.22 days. Pre-ovipositional, ovipositional and post ovipositional period ranged from 2-3 (2.68 ± 0.32), 3-4 (3.02± 0.16) and 3-4 days (3.82 ± 0.65), respectively. Total life cycle of males and females was observed as 33.32 and 34.75 days, respectively.